Clinical effects after subgingival polishing with a non-aggressive ultrasonic device in initial therapy - Maren Kahl (Blackwell Synergy, 2007)
Objectives: The Vectors ultrasonic system provides root debridement supported by different abrasive irrigation fluids. The aim of this study was to investigate the clinical outcome of initial therapy with subgingival low-abrasive debridement. Material and Methods: Twenty patients, who had at least two teeth with pocket depths 45mm in each quadrant, took part in this prospective randomized clinical study. Patients were treated in a split-mouth design as one test quadrant (1) subgingivally with Vectort fluid polish (VU-H) and as three control quadrants, (2) with only supragingival polishing (PO-H), (3) with hand instruments (HI-H) performed by a hygienist and (4) with hand instruments (HI-D) performed by a dentist. At baseline, 3 and 6 months after treatment, pocket depths and attachment levels (ALs) were measured and bleeding on probing (BOP) was recorded. Results: At 6-month evaluation, all groups showed an improvement in clinical parameters. No statistically significant differences in any of the investigated parameters could be observed between the Vector group and the hand scaling groups, or when comparing the results of the two different operators. Conclusion: This study demonstrates that Vectort treatment with polishing fluid was able to reduce pocket depths and the prevalence of BOP and improve clinical AL in a similar way as scaling with curettes.